Analisis Pengaruh Pengangguran dan Pertumbuhan Ekonomi terhadap Kemiskinan di Indonesia - Siti Kharisatul Ulya; Rindiani Rindiani; Gustina Masitoh; Chika Dwi Oktaviani; Aditya Reza Rezola (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Poverty is a global social problem that hinders human progress and welfare. This issue is very complex and has been going on for a long time, especially felt by people in developing countries such as Indonesia. Thereforevpoverty alleviation efforts must continue to be carried out through policies and concrete steps in their implementation. Based on various theories and previous research results, there are many factors that influence the level of poverty. Such as population, per capita income, limited resources, low levels of education, and lack of employment opportunities. Research shows that population growth is significantly correlated with increasing levels of open unemployment. Meanwhile, economic growth actually shows a negative effect on the unemployment rate. The interaction between population growth and economic conditions aiso has an impact on the level of open unemployment. This indicates that regional and city governments need to pay more attention to handling this problem. To encourage regional economic growth and control the rate of population growth, financial investment must be accompanied by the creation of new jobs. Thus, the community will have more job opportunities, so that unemployment and poverty can be suppressed.